A Mixed Integer Programming Approach for Transitioning from Open-pit to Underground Mining - Chung, Joyce Sze Yee (Curtin University, 2020)
This thesis contributes the mathematical models to solve the transition problem that derives the optimal production scheduling strategy for open-pit and underground mining simultaneously. A new hierarchical clustering algorithm is also presented to manage the large-scale instances of the problem. The implementations at hypothetical and realistic data sets confirm the value of proposed models.